Risk of Chronic Low Back Pain Among Parturients Who Undergo Cesarean Delivery With Neuraxial Anesthesia: A Nationwide Population-Based Retrospective Cohort Study - Chia, Yuan-Yi (Medicine (Baltimore), 2016)
To investigate the risk of chronic low back pain (LBP) in parturients undergoing cesarean delivery (CD) with neuraxial anesthesia (NA). LBP is common during pregnancy and also after delivery, but its etiology is poorly understood. Previous studies that investigated the correlation between epidural labor analgesia and chronic low back pain were inconclusive. These studies lacked objective diagnostic criteria for LBP and did not exclude possible confounders. We performed this nationwide population-based retrospective cohort study to explore the relationship between CD with NA and subsequent LBP. From the Taiwan National Health Insurance Research Database (NHIRD), we identified all primiparas who had given birth between January 1, 2000 and December 31, 2013. Using the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) procedure codes, we identified the women who had vaginal delivery (VD) and those who had CD. The mode of anesthesia was ascertained by the NHI codes. Multivariable logistic regression was used to estimate the odds of postpartum LBP in women undergoing CD with NA compared with those having VD. The outcome was a diagnosis of LBP according to the first ICD-9-CM diagnosis code. The patients were observed for 3 years after delivery or until diagnosis of postpartum LBP, withdrawal from the NHI system, death, or December 31, 2013. Of the 61,027 primiparas who underwent delivery during the observation period, 40,057 were eligible for inclusion in the study. Of these women, 27,097 (67.6%) received VD, 8662 (21.6%) received CD with spinal anesthesia, and 4298 (10.7%) received CD with epidural anesthesia (EA). Women who received CD with EA were found to have higher risk of LBP than did women who received VD, with the adjusted OR being 1.26 (95% CI: 1.17–1.34). CD with EA might increase the risk of subsequent chronic LBP.